2008
DOI: 10.1051/dst:2008008
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant milk components of Bactrian camel (Camelus bactrianus), dromedary (Camelus dromedarius) and hybrids

Abstract: -In Kazakhstan, the cohabitation of Bactrian camels, dromedaries and their hybrids is a common feature even within farms. The physico-chemical composition of 147 milk samples from 57 Bactrians, 70 dromedaries and 20 hybrids was determined. The samples came from 4 different regions and were collected at 4 different seasons within a year. Compared with dromedary, Bactrian camel milk had significantly higher fat (6.67 vs. 5.94%), vitamin C (177 vs. 152 mg·L −1 ), calcium (1.30 vs. 1.16 g·L −1 ) and phosphorus (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 12 publications
12
34
0
Order By: Relevance
“…Our results showed that the grand mean value of protein was found to be 4.02±0.1% and ranging from 3±0.3 to 4.5±0.2% (table 1). Protein content recorded in this study was agreed with the value reported by Faye et al (2008) and Konuspayeva et al (2010) Guliye et al (2000). The chloride content of camel's milk as shown in Table 1 varied from 0.14±0.008 and 0.16±0.003% with grand mean of 0.15±0.003%.…”
Section: Results and Discussion Chemical Analysis Of Camel's Milksupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that the grand mean value of protein was found to be 4.02±0.1% and ranging from 3±0.3 to 4.5±0.2% (table 1). Protein content recorded in this study was agreed with the value reported by Faye et al (2008) and Konuspayeva et al (2010) Guliye et al (2000). The chloride content of camel's milk as shown in Table 1 varied from 0.14±0.008 and 0.16±0.003% with grand mean of 0.15±0.003%.…”
Section: Results and Discussion Chemical Analysis Of Camel's Milksupporting
confidence: 93%
“…Mean values for total solid contents of camel's milk varied from 9.7±0.3 to 12.5±0.7% with grand mean of 10.8±0.3% (Table 1). These results were comparable to Faye et al (2008) and Farah (1993) while, they were lower than those reported by Moustafa et al (2000); El Shaer and El Ganzoury (2008); and higher than what reported by Omer and El-Tinay (2009); Shuiep et al (2008).…”
Section: Results and Discussion Chemical Analysis Of Camel's Milksupporting
confidence: 70%
“…This zone is characterized by few rainfall (<150 mm per year) and huge variations between summer (average of 28°C with some peaks over 40°C) and winter temperature (average of -17°C with some peaks under -30°C). According to Faye et al (2008), the following definition was used to identify the different genetic variants of camels: Bactrian and Dromedary are pure animals of the species Camelus bactrianus and Camelus dromedarius respectively. Iner is a F1 hybrid produced by a female dromedary and a Bactrian male, Nar is a F1 hybrid of Bactrian female and a dromedary male and finally F2 hybrids (Kospak).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, Bactrian camels are known to be less productive. A comparison of milk composition between both species in different Kazakh herds (Faye et al, 2008) showed increased fat and protein content in milk of Bactrian camels in comparison to dromedaries and lower milk density in Bactrian compared to this density in hybrids. Nevertheless, the main product of Kazakh camel breeder is shubat, a fermented product based on the whole milk what make the breeder sensitive to improve especially the milk yield of their animals.…”
Section: Introductionmentioning
confidence: 97%
“…However, in some cases, they are cohabiting in the same country, even in the same farm for example in Kazakhstan (Faye et al, 2008). In India, the double humped camel is only distributed in Nobra valley, a cold arid region of Ladakh in Jammu and Kashmir State.…”
Section: Introductionmentioning
confidence: 99%